From mammy to Miss America and beyond : cultural images and the shaping of US social policy - Jewell, K. Sue. (London ; New York : Routledge, 2002)
How do the mass media contribute to the social and economic advantages of the privileged and the subjection of African American women? Does America really care about providing equal opportunities for African American women? Passionately written and supported with detailed evidence this book shows the deeply rooted abiding cancer of oppresion in American society. It reveals the formal and informal ways in which African American women have been exluded from equal participation before and after the time of slavery. It will shock many who complacently believe that America is already a land.
Includes bibliographical references and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: African American women; United States -- Social policy -- 1980-1993.; Noires américaines.; États-Unis -- Politique sociale -- 1981-1993.; SOCIAL SCIENCE -- Women's Studies; African American women; Social policy; United States; 1980-1993